Internalization of Wasathiyyah Characters Through Rohis Extracurriculars - Lilis Nurhayati; Supiana Supiana; Aan Hasanah; Mohamad Erihadiana (International Journal of Social Service and Research, 2022)
Adolescent students have psychological conditions that are easily affected because they are experiencing mental shock, a period of mental growth and feelings. Among those who can affect it is extreme understanding in religion. The entry of extreme understanding in religion includes through the extracurricular Rohis. This there needs to be an effort to internalize the character of wasathiyyah in students, especially in Rohis extracurricular activities. This research aims to identify the objectives, programs, program implementation, supporting factors and inhibiting factors and the success of the internal programisasai character wasathiyyah in rohis extracurricular. The approach used in this research is qualitative by analytical desktiptif methods. Data collection is carried out through observation, interviews and documentation studies. The results and conclusions of this study are: 1) The purpose of internalizing wasathiyyah characters in Rohis extracurriculars is in line with the vision of the school's mission and has led to the formation of wasathiyyah characters. 2) Program in the form of Islamic study activities, whiteness, muhadoroh and mentoring, 3) Implementation of wasathiyyah character internalization activities program in Rohis extracurriculars with teaching, motivating, habituation, and study methods. 4) Supporting factors in the form of support of principals and teachers, initiatives and ghiroh of Rohis trustees, financing and availability of infrastructure, cooperation with NGOs (NonGovernment Organisation) and alumni cooperation. Inhibiting factors are the lack of motivation of some Rohis members in activities, misconceptions about moderation, the influence of less moderate alumni and less moderate media content. 5) Successful wasathiyyah character internalization program in Rohis extracurricular at SMAN 2 Bandung and SMKN 15 Bandung It was shown by the increase in the good attitude of Rohis members at the school in terms of national commitment, tolerance and anti-violence, after participating in study, whiteness, muhadoroh, and mentoring activities.